A Multidisciplinary Look at Menopause 2017
DOI: 10.5772/intechopen.69541
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phytoestrogens for the Treatment of Psychiatric Symptoms Associated with Menopause Transition

Abstract: Menopause transition is recognized as a vulnerable period in women life to develop or aggravate symptoms of psychiatric disorders. Several treatments including antidepressants and hormonal restitution with estrogens have been suggested to ameliorate the symptoms. Also, in this period of life is frequent the use of other drugs to treat is also frequent the use of other drugs to treat comorbid pathologies that might even increase the risk of drug-drug interactions. Literature reports that some phytochemicals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Due to its structural similarity to 17β-estradiol, GEN can activate estrogen receptors and is considered as a phytoestrogen [17]. Therefore, numerous dietary supplements contain GEN, which are applied in the alternative treatment of perimenopausal, menopausal, and post-menopausal symptoms [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its structural similarity to 17β-estradiol, GEN can activate estrogen receptors and is considered as a phytoestrogen [17]. Therefore, numerous dietary supplements contain GEN, which are applied in the alternative treatment of perimenopausal, menopausal, and post-menopausal symptoms [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens are biologically active plant-derived compounds that are similar in chemical structure to 17β-estradiol and mimic estrogen-like properties [7]. Among the phytoestrogens, isoflavones and lignans are commonly used to relieve menopausal symptoms, as they are abundant in fruits, vegetables, legumes, and soy [8,9]. A study on soy intake in various countries revealed that the average daily soy intake is nine times higher in Asian countries compared to North American and European countries, resulting in a higher life expectancy on average [10].…”
Section: Introductionmentioning
confidence: 99%
“…Functional foods contain many bioactive compounds as phytochemicals that proved their health effects (Fouad et al 2018). Phytochemicals are results of secondary metabolism of a plant which are biologically active in humans and other animal species assuming more prominent valuable effects in health more than just nutritional properties (Gonzalez-Laredo et al 2012).…”
Section: Discussionmentioning
confidence: 99%